Impact of motivational factors on knowledge sharing behaviour of managers in Ready Made Garments (RMG) Industry of Bangladesh - Islam, Md Asadul; Jantan, Amer Hamzah; Md Khan, Arif; Rahman, Md Habibur; Monshi, Osman (Academy of Business and Retail Management (ABRM), 2018)
The study aimed to examine the impact of motivational factors on the knowledge sharing behaviour of managers in the Ready-Made Garments (RMG) industry of Bangladesh. Everyone has knowledge and can be part of knowledge sharing specially in organizations where employees need knowledge from the seniors or other personnel to perform better. However, barriers in the knowledge sharing process are common while some motivators could be effective to overcome those barriers and motivate individuals to share their knowledge with others in the organisations. This study integrates motivational perspectives into the Theory of Planned Behaviour (TPB) to examine the impact of both intrinsic and extrinsic motivators on managers’ knowledge sharing behaviour in selected organisational contexts. The study used a quantitative strategy and a cross- sectional survey method for data collection from 110 respondents comprising general managers, product managers, shift managers, quality managers and line managers from randomly selected top 30 RMG organizations in Dhaka, Bangladesh. The results showed that among the selected motivational factors, enjoyment in helping others was highly associated with knowledge sharing behaviour of managers in RMG organizations. However, expected organizational rewards, reciprocal benefits and knowledge self-efficacy have a moderate level of impact on managers’ knowledge sharing behaviour.